Kewarganegaraan Digital Pada Era Globalisasi Di Indonesia - Lusi Tutur Mulia (Iuris Studia: Jurnal Kajian Hukum, 2023)
In the current era of globalization, everything experiences dynamics and developments towards digital, including citizenship in Indonesia. The concern of Digital Citizenship in the Industrial Age 4.0 is that digital technology can accelerate the pace of globalization and make the world more connected. The use of the digital world in civics education in tertiary institutions is a necessity that must be responded to by tertiary institutions. Citizenship education courses which are personality development courses need to be creatively and innovatively engineered as an effort to respond to the times that are synonymous with advances in information technology. For this reason, the concept of digital citizenship needs to be integrated into civics education courses in tertiary institutions by updating learning tools with the concept of digital citizenship and implementing learning approaches by taking into account scientific background